2020
DOI: 10.18784/smart.v6i1.988
|View full text |Cite
|
Sign up to set email alerts
|

Penguatan Toleransi dan Identitas Sosial Melalui Halalbihalal Lintas Agama Pada Masyarakat Kampung Gendingan, Yogyakarta

Abstract: Religious plurality has been a challenge in building tolerance and religious harmony in Indonesia. But people has a way to maintain social integration, among which is the tradition of halal bihalal on Eid Mubarak momentum. In Java, it can strengthen good relations between individuals and even among different religions, as shown by Muslims and Christians in Gendingan, Yogyakarta. This study aimed at revealing how the halal bihalal phenomonon across religions in Gendingan could serve as a driving force for relig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
0
9
0
2
Order By: Relevance
“…Through this experience, they can develop an attitude of tolerance, and respect for diversity, and know and respect other people's cultures. Halal bi halal can develop the character of students such as respecting diversity, nationalism, discipline, caring, and responsibility (Faidi, 2020;Napsiah & Sanityastuti, 2020;Rahmawati & Haryanto, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Through this experience, they can develop an attitude of tolerance, and respect for diversity, and know and respect other people's cultures. Halal bi halal can develop the character of students such as respecting diversity, nationalism, discipline, caring, and responsibility (Faidi, 2020;Napsiah & Sanityastuti, 2020;Rahmawati & Haryanto, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…These characteristics further direct individuals to easily accept differences in interpersonal relations (Sztejnberg & Jasiński, 2018). Moreover, previous studies have shown that interfaith friendships can be established when individuals respect one another, are open to differences, consider each other's feelings, and are accustomed to doing activities together (Al-Gazali, 2022;Harmi, 2019;Rahmawati & Haryanto, 2020;Utami et al, 2021). These conditions can be considered indicators of an individual's readiness to respond to differences in their environment, including differences in religion (Sztejnberg & Jasiński, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This approach fosters tolerance through positive activities that enable direct interactions between two or more groups. This approach focuses on developing tolerance and aims to change the existing stigma towards a more positive direction for each individual (Al-Gazali, 2022;Rahmawati & Haryanto, 2020). The hope is that individuals will form high-quality interfaith friendships based on their tolerance and the absence of stigma that disrupts interfaith friendships.…”
Section: Discussionmentioning
confidence: 99%
“…Memperkuat identitas beragama dalam budaya siswa-siswi berarti memberikan ruang dan dukungan untuk siswa-siswi mengembangkan pemahaman yang lebih dalam tentang agama dan budaya mereka sendiri, serta memberdayakan mereka untuk menghargai dan memperkuat identitas tersebut (Rahmawati, A., & Haryanto, 2020). Hal ini penting karena identitas agama dan budaya merupakan bagian integral dari diri seseorang dan dapat memberikan fondasi yang kuat untuk pengembangan pribadi dan kesejahteraan sosial.…”
Section: Memperkuat Identitas Beragama Dalam Budaya Siswaunclassified